Faktor-Faktor yang Berhubungan dengan Perilaku Berisiko terhadap Kesehatan Reproduksi Remaja: Factors of Risky Health Behaviors of Adolescents in the Sukabumi Region - Soejarwo, Fazar Kumaladewi; Apreliasari, Helmy; Risnawati (Journal of Holistics and Health Sciences, 2025)
Adolescent reproductive health is a healthy condition involving the reproductive systems, functions, components and processes possessed by adolescents. Adolescents who are unable to maintain their reproductive health can lead to risky behavior, risky behavior, which is defined as a behavior that is risky to health. The aim of this study is to determine the relationship between the role of parents, the role of teachers, the role of health workers on the risk behavior of adolescent reproductive health at YASPIM Vocational High School 2020. Adolescent reproductive health can also be defined as a healthy condition that concerns the reproductive systems, functions and processes of adolescents. Behavior is a reaction / activity due to stimulation by a person to something, which can be observed or cannot be observed by others. Role is a form of behavior expected of a person in certain social situations. This research is a descriptive study with a cross-sectional design, as it takes samples from one population, namely Class X of Yaspim Vocational School, using total sampling technique amounting to 88 people. The instrument used is a questionnaire with chi-square data analysis technique. The validity test results show that the table r value is 0.444. If the calculated r value > table r, it means it is valid. The research results indicate that there is a relationship between reproductive health risk behaviors and the role of parents with a value of (p=0.009 with OR 0.04). There is a relationship between reproductive health risk behaviors and the role of teachers with a value of (p=0.001 with OR 0.05), and there is a relationship between reproductive health risk behaviors and the role of healthcare providers with a value of (p=0.005 with OR 0.06). The author hopes that parents can increase their role towards adolescents, and for teachers to be able to provide reproductive health knowledge for students, as well as health workers to improve the promotion of reproductive health for adolescents.   ABSTRAK Kesehatan reproduksi remaja adalah suatu kondisi sehat yang menyangkut sistem, fungsi, komponen, dan proses  reproduksi yang dimiliki oleh remaja. Remaja yang tidak dapat menjaga kesehatan reproduksinya dapat menimbulkan perilaku berisiko, Perilaku berisiko, yang dimaksud  adalah perilaku yang berisiko terhadap kesehatan Tujuan penelitian ini mengetahui hubungan peran orangtua, peran guru, peran petugas kesehatan terhadap perilaku beresiko kesehatan reproduksi remaja SMK YASPIM Sukabumi Tahun 2024. Kesehatan reproduksi remaja dapat diartikan juga suatu keadaan  sehat yang menyangkut sistem, fungsi dan proses reproduksi yang dimiliki oleh remaja. perilaku adalah reaksi/aktivitas karena rangsangan yang dilakukan seseorang terhadap suatu hal, baik yang dapat diamati atau tidak dapat diamati oleh orang lain. Peran adalah bentuk dari perilaku yang diharapkan dari seseorang pada situasi sosial tertentu.  Penelitian ini merupakan penelitian deskriptif dengan desain cross sectional, karena mengambil sampel dari satu populasi yaitu Kelas X SMK Yaspim dengan teknik total sampling berjumlah 88 orang. Instrumen yang digunakan adalah kuesioner dengan teknik analisa data chi square. Hasil uji validitas diperoleh angka r tabel sebesar 0,444. Jika nilai r hitung > r tabel berarti valid.  Hasil penelitian menunjukkan bahwa Ada Hubungan Antara Perilaku Beresiko Kesehatan Reproduksi dengan Peran Orang Tua diperoleh nilai (p= 0,009 dengan OR 0,04). Ada Hubungan Antara Perilaku Beresiko Kesehatan Reproduksi dengan Peran Guru diperoleh nilai (p= 0,001 dengan OR 0,05), dan Ada Hubungan Antara Perilaku Beresiko Kesehatan Reproduksi dengan Peran Tenaga Kesehatan diperoleh nilai (p= 0,005 dengan OR 0,06). Penulis mengharapkan orangtua dapat meningkatkan peran nya terhadap anak remaja, dan bagi para guru agar dapat memeberikan pengetahuan kesehatan reproduksi untuk para siswanay, serta petugas kesehatan dapat meningkatkan promosi kesehatan reproduksi untuk remaja.